1998
DOI: 10.1097/00000542-199802000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Transfusion Practice for Coronary Artery Bypass Surgery Persists Despite National Consensus Guidelines 

Abstract: Institutions continue to vary significantly in their transfusion practices for CABG surgery. A more rational and conservative approach to transfusion practice at the institutional level is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(68 citation statements)
references
References 8 publications
1
63
0
4
Order By: Relevance
“…Transfusion rates during CABG vary between 0 and 100% [1,2,6,22]. Major benefit of prophylactic TA may not be found in institutions with low transfusion rates.…”
Section: Discussionmentioning
confidence: 99%
“…Transfusion rates during CABG vary between 0 and 100% [1,2,6,22]. Major benefit of prophylactic TA may not be found in institutions with low transfusion rates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multi-institution al study by Stover and colleagues showed that red cell transfusions varied by center, both in the percentage of patients receiving transfusions (17 -92%) and the number of units transfused (0 -4 units). 11 In this 24-center study, the variation could not be explained by patient variables, but rather, it was institutionally dependent. According to Spiess and colleagues, transfusion practices vary because neither an optimal Hct nor uniform transfusion criteria have been established.…”
mentioning
confidence: 74%
“…275,276 Newer research has shown that blood transfusion in the perioperative period actually has deleterious effects. It has been associated with a decrease in survival rates, with some studies citing up to a 70% increase in late mortality.…”
Section: Blood Transfusionmentioning
confidence: 99%